A cultural study of Disney's Star Wars : theorizing circuit of culture - Vaidya, Ruta (2019)
Using Star Wars as a case study, this thesis examines the cultural circulation of morality through discourses related to the Star Wars films and a range of the transmedia storytelling universe such as toys and merchandizing activities. My aim is to analyse the social and cultural significance of trust and loyalty as mutually reinforcing morals before and after Star Wars’ acquisitions by Disney. This thesis explores the similarities and differences in the ways that Lucasfilm (under the leadership of George Lucas) and Disney, separately perceive and circulate moral meanings through Star Wars films, toys and other merchandize and the processes and practices involved in the construction of morals. To study this phenomenon, the thesis adopts the theoretical and methodological framework of the circuit of culture to analyse four distinct yet overlapping and non-linear moments or processes: representation, production, consumption and identities. The thesis adds to a deeper sociological understanding of the meaning-making processes of a cultural text when handled by two different cultural industries. In adopting the circuit of culture, this thesis offers a unique understanding of the cultural complexity of Star Wars through the articulation of the interconnected cultural processes. Considering the acquisitions of Star Wars by Disney as a recent phenomenon, this thesis will contribute empirically to an understanding of the memoir of Star Wars as a moral narrative, analyzed through the various cultural processes that enable multiple and varied meanings for a text. To achieve this methodologically, this study employs an analysis of various discourses surrounding Star Wars when handled by Lucasfilm and Disney, respectively. In acknowledging the importance of film as a primary site to examine the conception of morals, I analyze discourses around the films and the various texts such as toys and merchandise, that are embedded within the cultural biography of Star Wars as a moral tale. This thesis focuses on four of the five moments/processes of the circuit of culture. In examining the production process, I examine a number of distinctive practices by focusing on narratives involving George Lucas, media and industry experts and producers at Lucasfilm and Disney. I discuss how trust and loyalty are embedded in various relationships within the process of cultural production enabling certain moral messages. An analysis of the representation processes involves taking into considering various accounts of Star Wars morals in terms of post-world war II discourses and its role in shaping Star Wars. These accounts add to a semiotic and a discursive understanding of morality as rooted in several analytic representations. An analysis of consumption involves examining two fan forums-the boardsnet.com, and thecantina.starwarsnewsnet.com to discuss how fans interpret and ‘consume’ morality through their interactions and engagement with films and toys and ways in which those morals meanings are decoded. In addition, I also examine content created by fans online to study their perceptions related to the moral messages and its circulation around Star Wars. In examining identities, I analyze the various social identities related to Star Wars, that is to say how people identify with the text and how Lucasfilm and Disney structure identities around Star Wars. I examine the identity in terms of how Star Wars has enabled fans/consumers to take up certain Star Wars identities by focusing on few discourses such as Star Wars’ communities with a focus on costuming clubs, Star Wars fan forums, Star Wars Identities Exhibition and Force Friday to show how trust and loyalty are interwoven into the processes of identification between the producers, consumers and the text. An articulation of these four processes is useful in providing an understanding of ways in which morality is disseminated in society through popular culture.